CDKA and CDKB kinases from Chlamydomonas reinhardtii are able to complement cdc28 temperature-sensitive mutants of Saccharomyces cerevisiae - Cízková, M; Pichová, A; Vítová, M; Hlavová, M; Hendrychová, J; Umysová, D; Gálová, E; Sevcovicová, A; Zachleder, V; Umen, J G; Bisová, K (Protoplasma, 2008)
Cyclin-dependent kinases (CDK) play a key role in coordinating cell division in all eukaryotes. We investigated the capability of cyclin-dependent kinases CDKA and CDKB from the green alga Chlamydomonas reinhardtii to complement a Saccharomyces cerevisiae cdc28 temperature-sensitive mutant. The full-length coding regions of algal CDKA and CDKB cDNA were amplified by RT-PCR and cloned into the yeast expression vector pYES-DEST52, yielding pYD52-CDKA and pYD52-CDKB. The S. cerevisiae cdc28-1N strain transformed with these constructs exhibited growth at 36 degrees C in inducing (galactose) medium, but not in repressing (glucose) medium. Microscopic observation showed that the complemented cells had the irregular cylindrical shape typical for G2 phase-arrested cells when grown on glucose at 36 degrees C, but appeared as normal budded cells when grown on galactose at 36 degrees C. Sequence analysis and complementation tests proved that both CDKA and CDKB are functional CDC28/cdc2 homologs in C. reinhardtii. The complementation of the mitotic phenotype of the S. cerevisiae cdc28-1N mutant suggests a mitotic role for both of the kinases.
Keywords: sekvenční seřazení; Transformation, Genetic; Genetic Complementation Test; transformace genetická; Temperature; Molecular Sequence Data; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; molekulární sekvence - údaje; teplota; mutace; CDC28 Protein Kinase, S cerevisiae; zvířata; Amino Acid Sequence; Chlamydomonas reinhardtii; Sequence Alignment; Saccharomyces cerevisiae; Animals; Mutation; proteinkinasa CDC28, S cerevisiae; testy genetické komplementace; sekvence aminokyselin